2005
DOI: 10.1111/j.1601-6343.2005.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro friction of stainless steel arch wire–bracket combinations in air and different aqueous solutions

Abstract: For all aqueous solutions a lower coefficient of friction was found compared to tests performed in ambient air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Such a reduction might shorten the treatment period and also improve anchorage control. 8 Friction between the bracket and archwire can cause up to 50% loss of force. 4,5,9 As a result, the desired tooth movement is slowed down or even inhibited.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Such a reduction might shorten the treatment period and also improve anchorage control. 8 Friction between the bracket and archwire can cause up to 50% loss of force. 4,5,9 As a result, the desired tooth movement is slowed down or even inhibited.…”
mentioning
confidence: 99%
“…2,10,11 Frictional resistance must therefore be kept to a minimum during sliding mechanics so that orthodontic tooth movement can be generated through optimal light forces with better patient comfort. 3 The theoretic considerations and clinical implications of friction during sliding in orthodontics demonstrated that this type of force depends on complex variables, such as bracket types (conventional vs. self-ligating), 2,5,8 angulation of archwire to bracket, 12 arch-wire 7 types, 13 dimensions and shape of the slot and the wire, 3,14 ligating force, 8,14 oscillating displacements, 2 repeated use of brackets, 11 and dry and wet environments. 4,15 Furthermore, it was reported that resistance to sliding or friction of an arch-wire-bracket assembly is a combined effect of 3 components namely, classical friction, elastic binding and/or physical notching.…”
mentioning
confidence: 99%
See 3 more Smart Citations